Tanda Bahaya Kepribadian Pemicu Penipuan - Saitri, Putu Wenny; Mendra, Ni Putu Yuria; Novitasari, Ni Luh Gde (Society, 2024)
The persistent issue of substantial losses due to fraud has heightened interest in exploring factors contributing to fraudulent behavior, with limited focus on the role of personality traits in fraud detection. This study investigates six personality traits—wrath, envy, attachment, pride, desire, and greed—that may influence an individual’s propensity for fraud. Using data collected through questionnaires distributed to microfinance institutions in Bali, a region experiencing a high prevalence of fraud cases, the study employs factor analysis to identify the contribution of these traits to fraudulent intentions. The findings reveal that wrath is the most significant predictor, followed by envy, attachment, pride, desire, and greed. The study underscores the practical implications of integrating personality assessments into organizational processes to enhance fraud detection and mitigation. This research offers a novel approach to understanding and addressing fraud in organizational settings by emphasizing personality traits as predictors of fraudulent intentions.